DAMPAK RUU LARANGAN MINUMAN BERALKOHOL TERHADAP USAHA PARIWISATA DI PROVINSI BALI - Sanjiwani, Putri Kusuma; Kerti Pujani, Luh Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022), 2023)
The draft Law on the Prohibition of Alcoholic Beverages has back to being a hot discussion in Indonesia. This news blows at the same time when COVID-19 pandemic is still hitting and has not been completely handled. The draft Law on the Prohibition of Alcoholic Beverages will limit the space for tourism entrepreneurs in Bali Province. The image of tourism in the eyes of foreign tourists who are close to lifestyle, like consuming alcoholic beverages will change. This research using normative legal research method, supported by primary and secondary data with data collection techniques carried out by observation, interviews, and literature study. This research analyzes draft law on the prohibition of alcoholic drinks so that it is necessary to emphasize several norms. This aims to avoid any controversy that will have a negative impact on tourism in Bali Province. Existence of accommodation business and food and beverage service business will be the most affected of this regulation is enacted.